Nivel de conocimiento de los padres sobre los principios de la Educación Inicial en instituciones estatales en el año 2020 - Araujo Reyes, Gloria María (2022)
The present research entitled: Level of knowledge of parents about the principles of Initial Education in state institutions in the year 2020, aimed to determine the level of knowledge of parents about the principles of initial education in state educational institutions in 2020. The research was basic with a simple descriptive design, applying a questionnaire on the principles of initial education, it was carried out with a sample population consisting of 16 PPFFof 4-year-old children of the I.E. N ° 11009 "Virgin of the Miraculous Medal" and for the 18 PPFF of the 4-year-old children of the I.E.I. "Pilgrims of the Lord", making a total of 34 PPFF. The results obtained indicate that the level of knowledge of parents about the principles of InitialEducation in state educational institutions in 2020 is that 67.65% have a medium level, 23.53%a low level and only 8.82% a high level.